Mengukur Potensi Wirausaha pada Program Pelatihan Kewirausahaan Mahasiswa Pendidikan Ekonomi - Muhammad Rapii (Universitas Islam Kadiri, 2019)
This study aims to to describe the potential entrepreneurs in the entrepreneurship training.The research results show that potential entrepreneurs in terms of various indicators show that the entrepreneurial potential students are in very high and high. categoryTo examine the potential owned, students need to realize how should students can develop the potential to have success in supporting activities. entrepreneurshipKnowledge of entrepreneurs have to support business success is only acquired to formal education in campus, but can also be obtained by, seminar activities training and. is self-taught